Force Majeure Sebagai Alasan Tidak Terpenuhinya Prestasi Akibat Corona Virus Disease 2019 (Covid-19) Dalam Usaha Jasa Konstruksi (Analisis Undang-Undang Nomor 2 Tahun 2017 Tentang Jasa Konstruksi) - Labibah Khoirunnisa; Ali Hanafiah Selian; Ipah Farihah (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
This thesis examines force majeure in construction service businesses influenced by the 2019 corona virus pandemic (COVID-19). This thesis explores the application of Article 47 paragraph (1) letter j of Law Number 2 of 2017 concerning Construction Services, which regulates coercion, to construction service enterprises affected by the development of the corona virus pandemic epidemic 2019 (COVID-19). This subject is relevant because the proliferation of COVID-19 in the construction service business has sparked a debate regarding the relevance of coercive conditions for construction service organizations facing impediments in completing their business activities. This is normative statutory legal research. (State and case) (case approach). This study employs literature to obtain data. This literature study collects documents and data for content analysis. According to the study, service businesses affected by the COVID-19 epidemic should use force majeure. This follows the classification of force majeure as relative, subjective, temporary, particular, and exclusive. Force majeure has legal ramifications in the construction service company, including contract termination, renegotiation, and worker compensation.